Direct Primary Care in 2015: A Survey with Selected Comparisons to 2005 Survey Data - Rowe, Kyle; Rowe, Whitney; Umbehr, Josh; Dong, Frank; Ablah, Elizabeth (Kansas Journal of Medicine, 2019)
Introduction. Direct primary care (DPC), a fee for membershiptype of practice, is an evolving innovative primary caredelivery model. Little is known about current membershipfees, insurance billing status, physician training, and patientpanel size in DPC practices. This study aimed to obtain currentdata for these variables, as well as additional demographicand financial indicators, and relate the findings to the HealthyPeople 2020 goals. It was predicted that DPC practices would(1) submit fewer claims to insurance, (2) have decreased membershipfees, (3) be primarily family medicine trained, and(4) have increased the projected patient panel size since 2005.Methods. An electronic survey was sent to DPC practices(n = 65) requesting location, membership fees, projectedpatient panel size, insurance billing status, training,and other demographic and financial indicators. Datawere aggregated, reported anonymously, and compared totwo prior characterizations of DPC practices done in 2005.Results. Thirty-eight of 65 (59%) practices responded to the2015 survey. The majority of respondents (84%) reported usingan EMR, offering physician email access (82%), 24-hour access(76%), same day appointments (92%), and wholesale labs (74%).Few respondents offered inpatient care (16%), obstetrics (3%),or financial/insurance consultant services. Eighty-eight percent(88%) of practices reported annual individual adult membershiprates between $500 and $1,499, decreased from 2005 where81% reported greater than a $1,500 annual fee. The proportion ofpractices who submit bills to insurance decreased from 75% in2005 to 11% in 2015. Fifty-six percent (56%) of practices reportedprojected patient panel size to be greater than 600, increasedfrom 40% in 2005. Family medicine physicians represented 87%of respondents, markedly different from 2005 when 62 - 77% ofDPC respondents were general internal medicine physicians.Conclusions. Most DPC practices no longer submit to insuranceand are family medicine trained. Comparedwith the previous sampling, DPC practices report decreasedmembership fees and increased projected panelsize. These trends may signify the DPC movement’sgrowth in application and scope. KS J Med 2017;10(1):3-6.